Lokaal 01 Antwerpen 2006. - Lokaal 01, Antwerpen (Antwerpen : Lokaal 01 Antwerpen, 2006)
Alberts, Michiel; Basten, Sabrina; Convert, Jean-Philippe; Maass, Gregory S.; Messchendorp, Wouter; Olbrechts, Thomas; Parker, Andrew; Re-enactment; Van San, Tamara; Vandaele, Kim.
Publicatie is resultaat van 8 intensieve werkperiodes in Lokaal 01_Antwerpen, 06.01.2006 - 19.10.2006
Nederlands
boek